Cyber Behaviors Among Heterosexual and Sexual Minority Youth: Subgroup Differences and Associations with Health Indicators - Luk, Jeremy W. (Cyberpsychol Behav Soc Netw, 2019)
To examine the associations of adolescent sexual orientation with cyber behaviors and health indicators 5 years later during young adulthood and test whether cyber behaviors contribute to sexual orientation health disparities. Data were drawn from Waves 2 and 7 from the NEXT Generational Health Study, a nationally representative cohort of U.S. adolescents (n = 2012). Multiple linear regressions were used to examine differences between sexual orientation subgroups (defined based on sexual attraction) in five cyber behaviors and five health indicators. Mediation analyses were conducted to examine whether cyber behaviors mediated the associations between bisexual attraction and health indicators. Relative to heterosexual peers, bisexual youth spent more time engaging in cyber behaviors and social media, and reported more psychosomatic symptoms and poorer general health. Gay and questioning males spent less time playing video games than heterosexual males. Bisexual females reported more depressive symptoms and less optimism and happiness than heterosexual females. Time spent on cyber behaviors and social media was a significant mediator of adolescent bisexual attraction and worse health outcomes in young adulthood. Frequency of cyber behaviors differed between sexual minority subgroups. Bisexual youth in particular had more psychosomatic symptoms and poorer general health. Engagement in cyber behaviors and social media use contributed to increased health disparities among bisexual youth.